Development of solid adsorbent materials for CO₂capture - Ogbuka, Chidi Premie (2013)
The application of solid adsorbents for gas separation in pre-combustion carbon capture from gasification processes has gained attention in recent times. This is due to the potential of the technology to reduce the overall energy penalty associated with the capture process. However, this requires the development of solid adsorbent materials with large selectivity, large adsorption capacity, fast adsorption kinetics for CO2 coupled with good mechanical strength and thermal stability. In this work, results on CO2 adsorption performance of three different types of adsorbents; a commercial activated carbon, phenolic resin activated carbons and zeolite templated carbons have been reported at atmospheric and high pressures conditions. The commercial activated carbon was obtained from Norit Carbons UK, the phenolic resin activated carbon was obtained from MAST Carbon Ltd., while the templated carbons were synthesized in the laboratory. A commercial activated carbon was used as bench mark for this study. Surface modification of these carbons was also undertaken and their CO2 uptake measurements at ambient and high pressure conditions were recorded. The commercial and templated carbons were modified by functionalising with amine group, while the phenolic resin carbon was modified by oxidation. The textural properties of the adsorbents was examined using the Micromeritics ASAP, while the CO2 adsorption capacities were conducted using the thermogravimetric analyser (TGA) and the High pressure volumetric analyser (HPVA). Textural properties of synthesized templated adsorbents were seen to depend on the textural characteristics of the parent material. The β-type zeolite produced the carbons with the best textural property. Increase in activation temperature and addition of furfuryl alcohol (FA) enhanced the surface area of most of the templated carbons. The textural property of all the adsorbents under study was seen to differently affect the CO2 uptake capacity at atmospheric (0.1 MPa) and high pressure conditions (up to 4 MPa). Micropore volume and surface area of the commercial activated carbons, phenolic resin activated carbons, and the templated carbons greatly influenced the adsorption trends recorded at ambient conditions. Total pore volumes positively influenced adsorption trend for templated carbons, but not the phenolic resin activated carbons at ambient and high pressure. This also positively influenced the adsorption trend for the commercial activated carbons, but at ambient conditions only. The surface area and the micropore volume have no effect on the adsorption trends for the templated carbons and the commercial activated carbons at high pressure conditions. However, these played a positive role in the adsorption capacities of the phenolic resin activated carbons at the same experimental conditions. Micropore volume and surface area of adsorbents play a major role on the adsorption trends recorded for the modified adsorbents at ambient conditions only. No trend was recorded for adsorption capacities at high pressure conditions. Only the oxidized phenolic resin activated carbon showed a positive adsorption trend with respect to total pore volume at high pressure condition. The amine modified commercial activated carbon showed no positive adsorption trend with respect to the total pore volume at both ambient and high pressure conditions, while the amine modified templated carbon showed no adsorption trend with respect to the textural properties at ambient and high pressure conditions. CO2 uptake measurements for the modified and unmodified templated carbon and phenolic resin carbon, were observed to be higher than those of the commercial activated carbon at ambient and high pressure conditions. Maximum CO2 uptake was recorded at 25 oC. At ambient pressure, the phenolic resin carbon (MC11) showed the highest CO2 uptake of approximately 3.3 mmol g-1, followed by the commercial activated carbon (2.4 mmol g-1), then, the templated carbon (2.4 mmol g-1). At high pressure, the templated carbons (β-AC7-2%) showed the highest CO2 uptake (21.3 mmol g-1), followed by phenolic resin carbon (MC4 - 12.2 mmol g-1), and the commercial activated carbon (6.6 mmol g-1). When samples were modified, the amine modified templated carbon and oxidized phenolic resin carbon showed the highest CO2 uptake of 2.9 mmol g-1 each at ambient pressure, followed by the commercial activated carbon (2.7 mmol g-1). At high pressure conditions, the oxidized phenolic resin carbon showed the highest (10.6 mmol g-1) uptake level, followed by the templated carbon (8.7 mmol g-1), and commercial activated carbon (6.5 mmol g-1).